Strainghtening Character Through Islamic Education in Millennial Era - Hafidurrahman, Moh (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
The rapid progress of science and technology which has a serious impact on the community change is called as millennial era. The impact requires us to determine the right attitude and in accordance with the values of Islam by creating three balances; spirit, soul (ratio) and body. Surely it gives good impact for the children brains development. But in other sides the children tend to be lazy to study in the school and lazy to read a book which is the window of the world. While our school still use board marker, white board, table, and chair in which these are not so interesting for them in comparing with the many tools existing in the mobile full of colors. While studying in the school provides only two colors (black and white) whereas there are thousand colors in mobiles. Moreover, many apps on mobile are far from the educational character that is the main soul as Muslim. A comprehensive and integrated learning method will be a solid foundation in straightening character in the millennial era, the need for teacher is to connect wisdom and blessings from God to students. The goal is that students have a good behavior in social life and fear of Allah S.W.T. Education is a help to awaken, arouse, grow, enable and empower students natural potential in having good character. Islamic education will give many stepping actions how to produce a good generation having good character gradually, from the education in pre-conception, post-conception, prenatal, and the post-natal education. There are five recommendations that Islam offer how to straighten the character i.e. knowing the good, feeling and loving the good, acting the good, modelling and exemplary, the last is repentance or regret.